Investigation of the electronic properties of a topological semimetal LaAuPb under uniaxial strain and hydrostatic pressure: A DFT approach - Babalola, M.I.; Jolayemi, O.R.; Enaroseha, Omamoke O.E.; Ejelonu, C.A. (The Journal of physics and chemistry of solids, 2024)
In this study, we utilized first-principles calculations to investigate the structural, electronic, mechanical, and vibrational properties of the topological semimetal LaAuPb. Our research delves into how uniaxial strain and hydrostatic pressure influence the electronic band structure of LaAuPb. We discovered that LaAuPb exhibits ductile behavior and maintains dynamic stability under various conditions. Upon introducing compressive strains of −6%, we observed a significant separation of degenerate states at the gamma point, which consequently led to the formation of a band gap. Similarly, the application of hydrostatic pressure at 16 GPa also resulted in the creation of a band gap by altering the electronic band structure. These findings suggest that both compressive strain and hydrostatic pressure can be effective in modulating the electronic properties of LaAuPb, potentially making it useful for applications requiring tunable electronic behavior. Conversely, when subject to tensile strain, no band gap formation was observed. Instead, there was a notable gradual overlap between the valence and conduction bands, indicating that tensile strain does not induce the same electronic separations as compressive strain or hydrostatic pressure. This asymmetrical response to different types of strain underscores the complex nature of LaAuPb's electronic properties and provides valuable insights for its potential use in electronic and mechanical applications. Overall, our findings contribute to the understanding of how external mechanical forces can be harnessed to control the electronic properties of topological semimetals like LaAuPb. •First principles calculation has been used to study the structural, electronic, mechanical and vibrational properties of the topological semimetal LaAuPb.•We further explored the effect of uniaxial strain and hydrostatic pressure on the electronic band structure of LaAuPb.•Our results reveal that LaAuPb is ductile in nature and it is dynamically stable. Degenerate states observed at the gamma point were separated as compressional strains of −6% was introduced as well as hydrostatic pressure of 16 GPa thereby creating a band gap.•As for the tensile strain, no gap was noticed instead there was gradual overlap of the valence and conduction bands.